Strategy of the Causes of Death of Dependents - ZHENG Da, TANG Shuang-bo, YE Wei-quan.et al. (Fayixue Zazhi, 2019)
Objective To discuss the methods and strategies to identify the causes of dependents’ deaths, as well as provide the experiences that can be used for reference and scientific basis for the forensic identification of the potentially growing deaths of the same kind in the future. Methods The 13 cases concerning death of dependents accepted by Sun Yat-sen University Forensic Center were collected, and the basic information of the dependents were statistically described. The nutritional status, environmental condition and medical care condition were evaluated according to dietary energy, living space, environment and medical treatment condition. Results Among the 13 dependents, there were 11 males and 2 females, with the oldest 74 and the youngest 9 and dwelling time was from 0.4 to 5.6 years. Forensic pathological examination showed that 13 dependents had infectious diseases and 11 were severely dystrophic. There were no fatal mechanical injuries or poisoning in dependents. Molecular pathological screening of 4 cases revealed no pathogenic variants of sudden death susceptible genes. The poor status of the diet, nutrition, living environment and medical care of these dependents were discovered. The direct cause of death of all 13 dependents was identified to be disease. The lack of nutrition, poor living environment and lack of medical care were thought to play a dominant role in causing the deaths of 12 dependants. Conclusion The death identification should follow the judicial procedure. In identification of the causes of death and analysis of the proportion of the affecting factors resulting in death, all factors, including nutrition,environment, medical care, injury and diseases, need to be considered.